UV Light Induced Fluorescence Recovery of GFP After Photobleaching in Microscopy Imaging - Prinčič, Griša G.; Jarc, Tina; Kristan, Katja; Kreft, Mateja Erdani; Veranič, Peter (Image Analysis and Stereology, 2022)
Fluorescence microscopy has become one of the most important tools for biologists to visualize and study organelles and molecules in a cell. Fluorescent markers are used to visualize specific molecules. One of the most used markers is green fluorescent protein (GFP), which can be expressed along with a protein of interest. However, it is known that the intensity of fluorescence decreases with observation time. To combat this problem, researchers and companies have developed protocols and additives to mitigate photobleaching. In this study, we tested the effects of the three most used culture media on photobleaching and developed a new approach of short-wavelength fluorescence recovery after photobleaching (FRAP). Photobleaching was analyzed by comparing pixel brightness on images taken with a fluorescence microscope. We determined photobleaching of GFP-expressing cells from images taken with a fluorescence microscope by comparing pixel brightness. Statistical analysis was performed to determine the average bleaching for specific culture media. The culture media analyzed had no significant effect on the photobleaching of GFP. However, a brief UV burst (15 sec) restores > 50% of the original fluorescence and neither increases ROS nor decreases cell viability. To avoid artifacts in image analysis and interpretation, our study suggests using this simple method of GFP fluorescence recovery with UV light induced FRAP to extend the fluorescence lifetime and imaging of GFP molecules.